ANALISIS KEBUTUHAN TRANSFORMASI DIGITAL SEKOLAH DASAR DALAM RANGKA MEWUJUDKAN TARGET SDGS PENDIDIKAN BERKUALITASDI SDN LEBAKWANGI BOGOR - Marisa; Tepati Hak Kewajiban; Siti Muyaroah; Izzul Fatawi (Smart Education, 2026)
This community service program aimed to accelerate the digitalisation of learning at SDN Lebakwangi through strengthening human resource capacity and information and communication technology (ICT) infrastructure. Before program implementation, a needs assessment was conducted involving 18 teachers to identify the school's initial conditions. The findings revealed a relatively high level of digital device ownership, with 16 teachers owning smartphones and 13 owning laptops. However, the integration of ICT into teaching and learning remained limited; 72.2% of teachers reported using technology only occasionally due to internet quota constraints. Approximately 72% of respondents relied on personal mobile data with network quality insufficient for video-based learning, while only 27% had access to the school’s Wi-Fi network. Teachers’ digital literacy competencies varied, with most falling within the moderate to high categories, although several teachers still demonstrated very low levels of digital competence. These findings served as the basis for implementing a differentiated training strategy. The analysis also indicated that technology use was predominantly focused on presentation tools such as Canva, PowerPoint, and YouTube (77%), whereas the utilization of interactive platforms, including learning management systems (LMS) and digital assessment applications, remained low (16%). Furthermore, 88.8% of teachers expressed a preference for hands-on training. Based on these findings, the community service team designed a program tailored to the partner school's needs to support sustainable digital transformation in learning.